Jurisdiction of Mental Health Tribunals to Provide Positive Remedies: Application, Challenges, and Prospects - Zuckerberg, Joaquin (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2011)
Modern mental health legislation protects the civil rights of the mentally ill by limiting the scope of permissible state interference with an individual’s autonomy. It also generally sets up mental health tribunals in charge of reviewing compliance with parts of the legislation. However, the legislation does not generally address the right to adequate mental health care. The latter (or its lack thereof) has increasingly become a source of debate among scholars and policy makers. The right to adequate care is increasingly being seen as the sine qua non of the civil rights of the mentally ill. This article explores recent Canadian jurisprudence dealing with the power of administrative tribunals to address constitutional and quasi-constitutional claims, and questions whether such power could give rise to a claim for adequate health care before mental health tribunals. It argues that, subject to some limited circumstances where mental tribunals have been given certain discretion to factor adequate care into their decisions, the recent Canadian jurisprudence does not significantly modify the limited remedies available before mental health tribunals.